2014
DOI: 10.3748/wjg.v20.i23.7277
|View full text |Cite
|
Sign up to set email alerts
|

Gallstones in patients with liver cirrhosis: Incidence, etiology, clinical and therapeutical aspects

Abstract: Gallstones occur in about one third of the patients having liver cirrhosis. Pigment gallstones are the most frequent type, while cholesterol stones represent about 15% of all stones in cirrhotics. Increased secretion of unconjugated bilirubin, increased hydrolysis of conjugated bilirubin in the bile, reduced secretion of bile acids and phospholipds in bile favor pigment lithogenesis in cirrhotics. Gallbladder hypomotility also contributes to lithogenesis. The most recent data regarding risk factors for gallsto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
3
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 69 publications
2
74
3
6
Order By: Relevance
“…[13,14,1618] Specifically, Conte et al [19] followed 618 cirrhotic patients and found that the probability of developing gallstones increased in a time-dependent manner. Moreover, Fornari et al [20] determined that cirrhosis is a risk factor for gallstones in males.…”
Section: Discussionmentioning
confidence: 99%
“…[13,14,1618] Specifically, Conte et al [19] followed 618 cirrhotic patients and found that the probability of developing gallstones increased in a time-dependent manner. Moreover, Fornari et al [20] determined that cirrhosis is a risk factor for gallstones in males.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Mortality from acute biliary pancreatitis (ABP) in the general population is 1-3%. [5][6][7] In addition, there is an increasing prevalence of gallstones as liver disease worsens within these patients. [5][6][7] In addition, there is an increasing prevalence of gallstones as liver disease worsens within these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Only a small proportion of cirrhotic patients harbour cholesterol stones. The factors leading to gallstone formation are the changes in bile composition (supersaturation of the bile with calcium bilirubinate for pigment stones or supersaturation with cholesterol for cholesterol stones), enhanced crystal nucleation in the presence of mucin and its congeners and gallbladder (GB) hypomotility (stasis) that allows crystals to grow into gallstones …”
Section: Introductionmentioning
confidence: 99%
“…Since laparoscopy was introduced in the late 1980s, it has been generally approved as the standard approach for cholecystectomies with the exception of end‐stage cirrhosis which was declared by NIH consensus statement in 1992 to be a contraindication . It was thought that the NIH came out with this concept because in the era prior to laparoscopic cholecystectomy (LC), published postoperative mortality in cirrhotic patients undergoing OC was 7.5–25.5% and patients with the most advanced liver disease were at the greatest risk.…”
Section: Introductionmentioning
confidence: 99%